Site selection for tidal turbine installation in the Strait of Malacca - Sakmani, Ahmad Safwan; Lam, Wei Haur; Hashim, Roslan; Chong, Heap Yih (Elsevier, 2013)
Malaysia is a coastal country, with a long coastline in Peninsular Malaysia connecting the Strait of Malacca in the west and the South China Sea to the east. The Strait of Malacca is a well-known waterway allowing the continuous supply of oil by tankers from the Middle East to the Far East, such as China, Japan and Korea. The Strait of Malacca is also a strategic location for the harnessing of the tidal stream energy due to its strong tidal current resources. The abundant tidal resource in the Strait of Malacca is a focus of research. However, none of the local researchers have investigated the site selection in the Strait of Malacca to propose the installation of a tidal turbine in detail. This study investigates the tidal stream resources and the topology of the Strait of Malacca by using the data from acoustic Doppler current profiler (ADCP) in order to propose Pulau Pangkor (Pangkor Island) for the site of the exploitation of the tidal stream energy.